Contextual understanding of care ethics in social entrepreneurship. Issue 5 (27th May 2022) - Sengupta, Subhanjan; Lehtimäki, Hanna
ABSTRACT: The purpose of this paper is to add a contextual understanding of care ethics to the nascent literature on ethics in social entrepreneurship. To this end, an interpretive study of social bricoleur entrepreneurs in rural India is presented and the constitutive effects of the enactment of care ethics are articulated. First, this enactment is examined as a relational practice between social entrepreneurs and local communities. Then, the notion of formative context is used to analyse how this enactment has expressions of human agency that constitute the societal context. Further, it is shown that context is not something that exists on its own but is instead enacted in the caring practices of social entrepreneurs. The micro-level practices of relating and the macro-level societal structures become malleable in the enactment of care ethics. This study has two major contributions. First, by departing from the notion of ethics as a characteristic of an individual, it shows how social entrepreneurs give and receive care through mutuality and human interaction. Second, by adding the analysis of sensemaking and formative context to care ethics, it deepens the understanding of context as conditions that facilitate the enactment of care ethics and is constituted by that enactment.